Efecto del proceso de deshidratación de la carambola (averrhoa carambola) como técnica postcosecha para asegurar la calidad y seguridad Alimentaria - Castro Guevara, Mayerling Dayanira (2023)
For the food industry, the postharvest processes that most fruits and vegetables comply with are inefficient, since the economic losses that these foods cause due to deterioration are due to low demand in the market that directly affects producers in the productive environment. For the investigation, it was proposed to determine the effect of the dehydration process of the carambola (Averrhoa Carambola) as a postharvest technique through tests and laboratory analysis to determine the quality and food safety that it offers in the field. The methodology used is the research was quantitative descriptive and experimental, where the carambola was characterized by means of a proximal analysis, before and after the dehydration process of three places in Ecuador using dehydration as a conservation method that allows food security, it was also determined the shelf life through a microbiological analysis. The results determined that the carambola from the city of Puyo presented better compositional characteristics and in the same way when dehydrating this fruit at a temperature of 60ºC, these parameters are better preserved with a stability sheet of up to 15 days without microbial loads. Regarding the results, it was concluded that the carambola from the Puyo area has better compositional characteristics and that when dehydrating the fruit at 60ºC in the drying process its properties are not denatured, emphasizing that this process should not exceed 6 hours to ensure the quality of the food